ST Segment Score on Initial Electrocardiogram (ECG) as a Predictor of In-Hospital Outcome of ST-Elevated Myocardial Infarction (STEMI) Patients - Karim, Md Mahmudul; Rahman Khan, HI Lutfur; Faruk, Md; Salam, Mohammad Addus (Medicine Today, 2022)
Introduction: The process of myocardial infarction progresses over several hours and therefore most patients present when it is still possible to salvage myocardium. ECG is usually a sensitive and specific way of confirming diagnosis. ST segment score (STSS) in myocardial infarction is emphasized but not often quantified. HJ Wellens gave cutoff for STSS in anterior wall MI (AWMI)of 12 mm and inferior wall MI (IWMI)of 7 mm. In this study the predictive value of ST Segment Score (STSS) with patients of STEMI on admission ECG & after thrombolysis had been assessed. Objectives: Identify patients at higher risk early in the course of their hospital admission & correlation of initial ECG and post thrombolysis ECG regarding clinical outcome. Materials and Methods:Considering inclusion and exclusion criteria 112 patients admitted in CCU, DMCH during october 2007 to september 2008 were studied of which 64 were inferior STEMI and 48 were anterior STEMI. Like admission ECG, after 90 minutes of starting thrombolytic,another ECG was recorded and calculated. Echocardiography was done for each patient before discharge. Data was collected in a pre-designed form. Results: The mean age of Group-I was 55.2±12.2 years and that of Group-II 56.9±14.1 years, Group-III 59.2±11.7 years,Group-IV 55.0±12.6 years. Of the 30 patients studied in Group-I 76.7% was male and 23.3% female. Smoking was the most prevalent (60% in Group I, 58.8% in Group II) risk factor. In post thrombolytic ECG shows that in Group-I mean sum of ST elevation decreased to 3.9 ± 1.1 mm from 4.8 ± 1.2 mm. which was approximately (45+14)% of ST resolution, in Group-II(50+19%),in Group-III (55+19)%, in Group-IV(45+23)%. Conclusion: Significant differences were seen in chest pain, killip class,arrhythmia, echocardiographic LVEF, duration of hospital stay in patients with AWMI & STSS above 12 mm and IWMI & STSS above 7 mm in comparison with below these level even after use of thrombolytics. Medicine Today 2022 Vol.34(2): 88-92